Key Audit Matters: Research on Auditor’s Reports Of Lithuanian Listed Companies - Vaicekauskas, Darius (Buhalterinės apskaitos teorija ir praktika, 2018)
[only abstract in English; full article and abstract in Lithuanian] Article investigates the presentation of key audit matters in independent auditor’s reports. The first theory based part of the article presents the problem of limited usefulness of auditor’s report and ex plains how this problem was addressed in the system of International Standards of Auditing with the introduction of the requirement to include the paragraph of key audit matters in auditor’s report issued on listed company’s financial statements (or when it is mandatory under the local laws). Further the concept of key audit matters is explained. In the empirical part of the article the results of the research on key audit matters included in the auditor’s reports of Lithuanian listed companies are presented. The typology of key audit matters is disclosed, while analysing the number, the content and the significance of key audit matters included in the research sample of auditor’s report. It can be concluded that key audit matters are those matters that, in the auditor’s professional judgment, were of most significance in the audit of the financial statements of the current period. Key audit matters are selected from matters communicated with those charged with governance. Audit firms of Lithuanian listed companies most often include one key audit matter in their auditor’s reports, while assessing the valuation of assets and revenue recognition as the areas of most significance during the course of the audit. The paragraph of key audit matters covers approximately one quarter of the content of the auditor’s report, indicating the informational significance of key audit matters and stressing a further need to improve their presentation.